THE TRANSFORMATIVE EFFECT OF SOUTH AFRICAN HIGHER EDUCATION POLICY FRAMEWORKS THROUGH THE LENS OF MARGARET ARCHER’S SOCIOLOGICAL CONCEPTS - Haruna Maama (RADJA PUBLIKA, 2023)
After the end of the apartheid regime, the South African Government and other stakeholders have made several commitments to enhance and transform the nation's educational system, particularly higher education. To achieve this, the government implemented several educational reforms, passed legislation, and established policies. Despite some discussions and debates surrounding educational improvement, there is still a lack of comprehensive analysis that examines the specific contributions, challenges, and potential challenges of these policy frameworks in driving positive transformations. Accordingly, this research examines the transformative impact of South African Higher Education policy frameworks using Margaret Archer's morphogenetic theory as an analytical framework. The study conducts a desktop document analysis of published literature, including policy documents from the South African government, to explore the contributions and challenges of these policy frameworks. The analysis reveals a lack of significant changes in agency, social, and cultural structures, indicating the absence of morphogenesis processes. Furthermore, there is a lack of commitment from various agents to the policy objectives, particularly evident in weaknesses in fulfilling mandates and the resulting institutional instability due to student protests. The study highlights that the anticipated impact of policies, strategies, and financial resources may have fallen short of expectations regarding the transformation process. The findings contribute to understanding the limitations and effectiveness of South African Higher Education policy frameworks, offering insights into the complex dynamics between structure, culture, and agency. This research informs policymakers, educators, and stakeholders involved in higher education by providing recommendations to enhance the transformative potential of these policy frameworks. The research has broader implications for understanding educational improvement and policy frameworks in other contexts, as the insights gained from this study can be applicable and valuable to similar settings facing challenges in educational reforms..